Programa de autonomia escolar: limites e possibilidades para a construção progressiva da autonomia financeira das escolas municipais de Maracanaú - Valentim, George Lopes (2024)
This work, a master's thesis in a Public Policy Evaluation course, analyzes the financial auton omy of schools in the city of Maracanaú, state of Ceará, entitled Programa de Autonomia Escolar (PAE). It aims to evaluate the aforementioned initiative, highlighting its limits and possibilities for the progressive construction of the school's financial autonomy. To achieve this objective, the path taken was the analysis of the impacts of the Program on the organization and functioning of the school and the identification of limiting aspects of the policy, proposing strategies for expand ing and/or improving the policy. It took as its starting point the context of the reform of the brazilian State (1995/1998) and the decentralization policies resulting from it, in particular the Programa Dinheiro Direto na Escola (PDDE), as an inducing policy (Diniz; Azevedo, 1997; Pereira, 1996, 2001), also receiving contributions regarding the following categories: school au tonomy, school financial autonomy, school financial management and democratic management (Gadotti, 1997; Menezes, 2001; Moreira, 2018; Moreira, Vieira, 2020, 2021). The methodologi cal path was inspired by Cohen and Franco (1993), using the case study as a method (Yin, 2001), considering the essential aspects of evaluating social policies in depth (Rodrigues, 2008). Thirty four subjects were interviewed, with data collected through interviews and analyzed using docu ment analysis (Neves, 1996) and content analysis (Bardin, 2010). It concludes that the policy in question contributes to improving objective working conditions at school, strengthening school autonomy and democratic school management, and can also contribute to local development, im proving the students learning, quality education and the population's quality of life.